A wizard of Earthsea - Le Guin, Ursula K., 1929-; Robbins, Ruth (New York : Bantam, 1984)
A boy grows to manhood while attempting to subdue the evil he unleashed on the world as an apprentice to the master wizard.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
6.1
5-8
7-9
Keywords: Coming of age -- Fiction; Fantasy; Magic -- Fiction; Wizards -- Fiction; Bildungsromans; Magic -- Fiction; Wizards -- Fiction; Fantastic fiction